Observing the dark universe with weak gravitational lensing - Robertson, NC (2019)
We are now entering into an era of huge cosmological data sets, with observations testing the current paradigm to high accuracy. By combining different probes of cosmology, we can access new information about our Universe and investigate the systematic effects that plague our ability to measure cosmology accurately. In this thesis we use weak gravitational lensing as a tool to measure the large scale structure in the Universe. First, we present the theoretical framework in which this thesis is set. We then detail the methodology required to measure the cross-correlation between galaxy weak lensing and cosmic microwave background (CMB) weak lensing data sets. In particular we highlight the impact of the complicated nature of galaxy weak lensing data and investigate ways to improve the signal-to-noise of the cross-correlation measurement using simulations.